The sustainability of empire in global perspective: The role of international trade patterns - Roberto Bonfatti (Center for Economic Studies and ifo Institute (CESifo), 2012)
European empires had two key economic aspects: the extraction of colonial wealth by colonizers, and the relevance of trade for the colonial economies. I build a simple model of decolonization that puts these two elements at centre stage. By controlling policy in the colony, the mother country can appropriate part of her wealth; the colony, however, can stage a successful revolution at a stochastic cost. I incorporate this mechanism in a three-country, two-good trade model where countries (the mother country, the colony and a third independent country) can decide whether to trade with each other, and revolution is expected to generate trade frictions between the mother country and the rebel colony. Thus, the attractiveness of revolution and the sustainability of empire come to depend on the capacity of the rebel colony to access international markets, which, in turn, depends on the economic fundamentals that shape the pattern of trade as well as the optimal trade policy of the third country. I present detailed historical evidence showing how to use this model to put a few important cases of decolonization in global perspective. My results have important implications for the debate on the economic legacy of colonial empires.
Keywords: D74; H77; F10; N40; 330; colonial trade; decolonization; international determinants of secession; American Revolution; independence of Spanish and Portuguese America; Großmacht; Nachhaltigkeit; Geschichte; Postkolonialismus; Internationale Wirtschaftsbeziehungen; Politische Unruhen; Mehr-Länder-Modell; Welt